Correlation of Age, Administration Method, and Amlodipine Dosage with the Risk of Side Effects in Hypertensive Patients - Tarapanjang, Tiara Rambu Renesia; Riwu, Magdarita; Lada, Christina Olly; Tallo Manafe, Derri Riskiyanti (Universitas Nusa Cendana, 2024)
Hypertension, known as the